Computational design of an amidase by combining the best electrostatic features of two promiscuous hydrolases. Issue 17 (29th March 2022) - Galmés, Miquel À.; Nödling, Alexander R.; He, Kaining; Luk, Louis Y. P.; Świderek, Katarzyna; Moliner, Vicent
Abstract : A computational strategy, based on combining the best electrostatic properties of enzymes with activity on a common reaction, is presented and applied to the re-design of the protein scaffold of an promiscuous esterase to enhance its secondary amidase activity. Abstract : While there has been emerging interest in designing new enzymes to solve practical challenges, computer-based options to redesign catalytically active proteins are rather limited. Here, a rational QM/MM molecular dynamics strategy based on combining the best electrostatic properties of enzymes with activity in a common reaction is presented. The computational protocol has been applied to the re-design of the protein scaffold of an existing promiscuous esterase from Bacillus subtilis Bs2 to enhance its secondary amidase activity. After the alignment of Bs2 with a non-homologous amidase Candida antarctica lipase B (CALB) within rotation quaternions, a relevant spatial aspartate residue of the latter was transferred to the former as a means to favor the electrostatics of transition state formation, where a clear separation of charges takes place. Deep computational insights, however, revealed a significant conformational change caused by the amino acid replacement, provoking a shift in the p K a of the inserted aspartate and counteracting the anticipated catalytic effect. This prediction was experimentally confirmed with a 1.3-fold increase in activity. The good agreement between theoretical and experimental results, as well as the linear correlation between the electrostatic properties and the activation energy barriers, suggest that the presented computational-based investigation can transform in an enzyme engineering approach.